Review of “score-on-doors” rating checklist for food safety inspection of meat vendors in Addis Ababa, Ethiopia - Amenu, Kebede; Keba, Abdi; Alonso, Silvia (CGIAR, 2025)
The International Livestock Research Institute (ILRI) and International Food Policy Research Institute (IFPRI) in collaboration with Addis Ababa Food and Drug Authority (AA-FDA) have implemented a food hygiene improvement project involving meat vendors in Addis Ababa from 2023 to early 2025 under two CGIAR initiatives on: One Health and Resilient Cities. A randomized controlled trial study involving 300 meat vendors showed that disclosure of food hygiene rating combined with training and technology provision can improve hygiene of meat vendor shops by reducing E. coli contamination. Considering these positive findings, ILRI and its partners organized a one-day stakeholder workshop on 30th of October 2025. The objective of the workshop was to further discuss the refinement of hygiene scoring and how disclosure of the scoring can help improve food safety in meat shops. For this purpose, ILRI invited food safety experts in Ethiopia to support the reviewing of the checklist and further refine for wider use. The experts who agree to engage were invited to take part in a twostep exercise. First, experts were asked to review a ‘score on doors’ checklist used to monitor specific hygiene indicators in meat shops. Second, experts who provided comments to the checklist were invited to attend a one-day workshop in Addis Ababa to refine the checklist and design a way forward for this research agenda.